The Ability to Implement TQM and Professional Development on Job Satisfaction Implications for the Performance of Tutors at Course Education Institutions in Serang City - Rohmawati, E. Ine Karlina; Yusuf, Furtasan Ali; Maliki, Budi Ilham; Rismaya, Nurimah (Asian Journal of Multidisciplinary Studies, 2024)
This research aims to analyze: the direct influence of TQm on tutor job satisfaction; the direct influence of professional development on tutor job satisfaction; the direct influence of TQM on tutor performance; the direct influence of professional development on tutor performance; the direct influence of job satisfaction on tutor performance; the indirect influence of TQM on tutor performance, through the intervening variable job satisfaction; and the indirect influence of professional development on the performance of course institute tutors in the city of Serang through the intervening variable job satisfaction. The method used in this research is that the type of research is quantitative research with a correlational approach that connects exogenous and endogenous variables either through intervening or direct variables. The research population was 1,420 people, with a sample of 225 respondents. Data was collected using a survey method and analyzed using Structural equational modeling (SEM) with the help of Smart PLS software. Based on the results of the analysis, it is concluded: that there is a direct influence between TQM on job satisfaction; there is a direct influence between professionalism development on job satisfaction; there is an influence of TQM on tutor performance both directly and through job satisfaction; there is an influence of professionalism development on performance, both directly and through job satisfaction; There is a direct influence of job satisfaction on performance.